Discovery of potent and selective inhibitors of calmodulin-dependent kinase II (CaMKII). Issue 3 (1st February 2018) - Koltun, Dmitry O.; Parkhill, Eric Q.; Kalla, Rao; Perry, Thao D.; Elzein, Elfatih; Li, Xiaofen; Simonovich, Scott P.; Ziebenhaus, Christopher; Hansen, Timothy R.; Marchand, Bruno; Hung, WaiLok K.; Lagpacan, Leanna; et al.
Graphical abstract: Abstract: We hereby disclose the discovery of inhibitors of CaMKII (7h and7i ) that are highly potent in rat ventricular myocytes, selective against hERG and other off-target kinases, while possessing good CaMKII tissue isoform selectivity (cardiac γ/δ vs. neuronal α/β). In vitro and in vivo ADME/PK studies demonstrated the suitability of these CaMKII inhibitors for PO (7h rat F = 73%) and IV pharmacological studies.